G-cleave LC3B biosensor: monitoring autophagy and assessing resveratrol's synergistic impact on doxorubicin-induced apoptosis in breast cancer cells - Liao, C; Long, Y; Tsai, M; Lin, C; Hsu, K; Lee, C (BioMed Central, 2024)
Autophagy, a crucial process in cancer, is closely intertwined with both tumor progression and drug resistance development. However, existing methods used to assess autophagy activity often pose invasiveness and time-related constraints, limiting their applicability in preclinical drug investigations. In this study, we developed a non-invasive autophagy detection system (NIADS-autophagy, also called G-cleave LC3B biosensor) by integrating a split-luciferase-based biosensor with an LC3B cleavage sequence, which swiftly identified classic autophagic triggers, such as Earle's Balanced Salt Solution and serum deprivation, through protease-mediated degradation pathways. The specificity of G-cleave LC3B biosensor was confirmed via CRISPR gene editing of pivotal autophagy regulator ATG4B, yielding diminished luciferase activity in MDA-MB-231 breast cancer cells. Notably, the G-cleave LC3B biosensor exhibited strong concordance with established autophagy metrics, encompassing LC3B lipidation, SQSTM1 degradation, and puncta accumulation analysis. To underscore the usage potential of the G-cleave LC3B biosensor, we discovered that resveratrol acts as a synergistic enhancer by significantly potentiating apoptosis in MDA-MB-231 cells when combined with doxorubicin treatment. Overall, the luminescence-based G-cleave LC3B biosensor presents a rapid and dependable avenue for determining autophagy activity, thereby facilitating high-throughput assessment of promising autophagy-associated anti-cancer therapies across diverse malignancies.